STRATEGI PEMBANGUNAN PERTANIAN DALAM RANGKA MENDUKUNG PROGRAM KETAHANAN PANGAN DI KABUPATEN KETAPANG - Nashar Setyabudi, Achmad (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2016)
The increase in population results in the emergence of problems to meet their food needs. In accordance with the problems faced, this study aims to analyze the profile of food independence at the research locus, and then formulate an alternative food development policy strategy at the research locus. This research was conducted in March-July 2015. The research locus was determined purposively, namely in Ketapang Regency. This study uses a type of research evaluation with descriptive presentation. The results showed that the amount of energy consumed by the population of Ketapang Regency reached 2,915 kcal / cap / day or 145.75 percent AKE (Energy Adequacy Rate). The availability of protein per capita reached 73.03 gr / capita / day or 146.06 percent from the National Standard. While the availability of fat is 58.07 gr / cap / day. The amount of fish consumption per capita is 35 kg / year, this realization is 90.91 percent of national fish consumption. To strengthen food security in Ketapang District, a model and strategy for food products is needed by integrating the utilization of all existing potential both in terms of natural resources, human resources, social affairs, cultural nobility and local wisdom and can solve the problems of food agribusiness that are faced from upstream to downstream, namely through: (1) Food Estate development carried out innovatively without limits in quantity and quality, (2) Maximizing the function of the Sustainable Food House Area (KRPL) as an innovative effort to use it and also replicating it. (3) To diversify in the food sector horizontally and vertically